Clean and renewable energy - Kalogirou, Soteris A. (My University, 2024)
In this chapter, various possible applications of renewable energy in cities and communities are presented. Being a clean form of energy, without any harmful emissions to the atmosphere, renewables effectively improve sustainability in the near and far future. Successful applications of renewables presented in this chapter include solar water heating, space heating and cooling systems, and photovoltaics and hybrid PV/T systems which provide both thermal and electrical energy. Another form of renewable energy systems used in buildings is the geothermal energy systems which employ ground heat exchangers in combination with heat pumps. These can supply both heating and cooling in buildings and communities. Besides the building application of the various renewable energy systems these are nowadays used more and more in district heating and cooling networks to satisfy either a district, a neigh-borhood, or a complete village or small city. Finally, the current status of these systems in the world is also presented to show the prospects for the future.
Keywords: District networks; Geothermal; Hybrid photovoltaics; Solar water; Space heating